Sub-optimal use of anti-malarial therapy for SLE in the Asia Pacific region: observations from the Asia Pacific lupus cohort - Kandane-Rathnayake, Rangi; Hoi, Alberta; Louthrenoo, Worawit; Chen, Yi-Hsing; Cho, Jiacai; Lateef, Aisha; Hamijoyo, Laniyati; Chan, Shirley; Luo, Shue Fen; Jan Wu, Yeong-Jian; Navarra, Sandra; Zamora, Leonid; et al. (Frontiers in Lupus, 2024)
Introduction The guidelines for management of patients with systemic lupus erythematosus (SLE) recommend the use of anti-malarial (AM) drugs [commonly hydroxychloroquine (HCQ)] in all patients, unless contraindicated. We evaluated the prevalence of AM use in patients with SLE in countries across the Asia Pacific region. Methods We used data from the Asia Pacific Lupus Collaboration (APLC) cohort, collected prospectively from SLE patients meeting ACR or/and SLICC criteria, between 2013 and 2020. Demographic factors were collected at enrolment; disease activity indicators (SLEDAI-2K, PGA, SFI) and medication (glucocorticoids (GC), immunosuppressants (IS) and AM) details were captured at enrolment and at routine visits, and organ damage was assessed at enrolment and at annual visits using SLICC/ACR Damage Index. We examined medication use in relation to clinical and serological activity, defined based on SLEDAI-2K. Results We analyzed 4,086 patients and 41,653 visits of data; 3,222 (79%) patients used AM at least once during observation (AM-ever users), but this proportion varied significantly between countries (31%–95%). Overall, the total number of visits with AM use was 27,474 (66%). AM-never users were older and had lower disease activity at study enrolment when compared with AM-ever users. AM-ever users had lower GC and IS exposure; experienced fewer severe flares, and less organ damage. Discussion AM use was suboptimal and varied significantly across countries, highlighting disparities between current practice and SLE management guidelines. This study further reiterates that patients who used AM during the study period had lower exposure to GC and IS and experienced fewer severe flares and organ damage.